Penerapan Senam Dismenore terhadap Skala Nyeri Haid Pada Remaja Putri di Wilayah Desa Jatiyoso Kabupaten Karanganyar - Distya Maharani; Sri Hartutik (STIKes Ibnu Sina Ajibarang, 2023)
Background: The problem of dysmenorrhea can be caused by lack of exercise, the age of menarche, the duration of menstruation, besides that the history of dysmenorrhea in the family is also a factor that can affect dysmenorrhea in adolescent girls. The incidence rate of dysmenorrhea in the world tends to be high. On average, more than 50% of teenagers suffer from dysmenorrhea. Dysmenorrhea gymnastics is a form of relaxation that is done to stretch the waist, abdominal and pelvic muscles that can provide comfort and can reduce pain. Objective : Knowing the change in the scale of pain in young women who experience dysmenorrhea before and after the application of dysmenorrhea. Method : This study uses a descriptive case study by observing 2 respondents of 17year old teenage girls who were given the implementation of dysmenorrhea exercises which was carried out during 3 meetings in 1 week with a time of ± 30 minutes per meeting. Result: After applying dysmenorrhea, there was a decrease in the pain scale and was included in the category of mild pain. Conclusion: This dysmenorrhea can reduce the scale of pain in young women who have dysmenorrhea.